INDICATORS ATTRIBUTES OF THE QUALITY OF THE SOIL IN SETTLEMENTS OF EUCALYPT FERTIRRIGATED IN THE VALE DO RIO DOCE - MG - dos SANTOS, Crisliane Aparecida Pereira; TÓTOLA, Marcos Rogério; BORGES, Arnaldo Chaer; KASUYA, Catarina Megumi (Scientia Agraria, 2009)
The objective of this work was to follow possible changes in the indicators attributes of the quality of soils in settlemens of eucalypt by means of use of irrigation and fertirrigation of effluent of a cellulose plant, by means of a mathematical model that express the Index of Quality of Sol (IQS), using microbiological and chemical attributes. Two experiment distinct were installed, both made use in subdivided parcels, being one in the valley position and the other in the slope position, in the city of Belo Oriente - MG, with classified soils as Fluvic Neosol and Yellow Latosol, respectively. The following treatments were considered: irrigation until the maximum evapotranspiration (Irrigation), fertirrigation until the maximum evapotranspiration with 100% of the fertilization recommended for the demand nutritional of the plant (Irrigation - Fertilization) and fertirrigation with effluent of cellulose (Irrigation - Effluent). Samples of soils of areas of eucalypt and two others considered as reference (secondary forest and pasture) had been collected in 2003, during two periods of the year (rainy and dry), under valley position and slope, and analyzed how much to the microbiological and chemical attributes for determination of the IQS. The chemical attributes showed more sensible to the effect of the use and management of the soil that time effect. The IQS presented similar behavior between the treatments only for the slope position (Yellow Latosol), but not for that valley position (Fluvic Neosol).